2018
DOI: 10.1002/bjs.10788
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and molecular classification of colorectal cancer and corresponding peritoneal metastases

Abstract: Significant enrichment for CMS4 was observed in colorectal peritoneal carcinomatosis. Surgical relevance Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) improves survival of selected patients with colorectal peritoneal carcinomatosis, but recurrence is common. Histopathological and molecular analysis of colorectal peritoneal carcinomatosis could provide clues for development of novel therapies. In this study, colorectal peritoneal carcinomatosis was found to be enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 29 publications
3
52
1
Order By: Relevance
“…RAS/RAF mutations alone have been inconsistently assessed in a few series of CRS/HIPEC, with contrasting results. [23][24][25][26][27][28][29][30] Analogously, primary tumor sidedness correlated with prognosis in two American series but not in one French series. [31][32][33][34] Our findings strongly suggest that both BRAF mutations and right-sided primary have to be taken into consideration, not only as prognostic factors in patients undergoing curative-intent treatment but also as stratification factors in future clinical trials.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…RAS/RAF mutations alone have been inconsistently assessed in a few series of CRS/HIPEC, with contrasting results. [23][24][25][26][27][28][29][30] Analogously, primary tumor sidedness correlated with prognosis in two American series but not in one French series. [31][32][33][34] Our findings strongly suggest that both BRAF mutations and right-sided primary have to be taken into consideration, not only as prognostic factors in patients undergoing curative-intent treatment but also as stratification factors in future clinical trials.…”
Section: Discussionmentioning
confidence: 86%
“…In previous literature series of CRC-PMs, analysis of mutations outside the KRAS exon 2 was not undertaken, 23 was limited to the BRAF V600E mutation, 24,25,31 was undertaken in a limited number of patients, 26,30 or was not specified. [27][28][29] Furthermore, three studies were multiinstitutional series, 25,27,29 with possible differences in sequencing and/or surgical procedures, and one study 31 also included appendiceal cancers, in which KRAS mutations are more frequent. 36 The proportions of KRASmutated (33-58%) and BRAF-mutated patients (8-13%) were comparable in the literature and our study, with the only exception being the series of Ubink et al, with a 25% BRAF mutation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Second, HIPEC is nearly always preceded by CRS which induces cytokine production that could also influence drug response. Third, intrapatient interlesion heterogeneity may provide an additional level of complexity that is not modelled in the present organoid collection. Despite these limitations, this model of PM from colorectal cancer is a robust in vitro system that allows rapid evaluation of existing and novel HIPEC strategies in a biologically relevant setting.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of a Dutch cohort has shown colorectal cancer peritoneal metastases to be enriched for the consensus molecular subtype (CMS) four or the mesenchymal subtype. Eight of twenty-four of these patients had mucinous adenocarcinoma [26]. In a review of clinical, morphological and molecular classification of colorectal cancer, Jass notes that mucinous differentiation is not specific to clinicopathological subtypes [27].…”
Section: Discussionmentioning
confidence: 99%